The Impact of Working Capital on Financial Performance Moderated by Dividend Policy and Financial Ratios: A Study of Manufacturing Companies in Indonesia - Lutfi Adnan Affif; Asfina Nor Husna; Henny Setyo Lestari; Farah Margaretha Leon (Majapahit Journal of Islamic Finance and Management, 2026)
This study aims to analyze the impact of working capital on financial performance moderated by dividend policy and financial ratios at manufacturing companies in Indonesia. This research method uses a panel data regression, utilizing Eviews 9.0 software for data processing. The sample for this study includes 47 technology and manufacturing companies listed on the IDX with consistent data available for the 2020–2024 observation period. This study adopts a hypothesis-testing design to analyze the effects of the Cash Conversion Cycle, Leverage, Sales Growth, and Investment Policy on Financial Performance (ROA). Additionally, the model incorporates Size and Inflation as control variables and Dividend Payout Ratio as the moderating variable.